Mining various genomic resources to resolve old alpha-taxonomy questions: A test of the species hypothesis of the Proteocephalus longicollis species complex (Cestoda: Platyhelminthes) from salmonid fishes - Brabec, Jan; Rochat, Eloïse C; Knudsen, Rune; Scholz, Tomáš; Blasco-Costa, Isabel (International journal for parasitology, 2023)
High-throughput sequencing strategies became commonly employed to study non-model parasites, but the corresponding genomes and transcriptomes were seldom mined following the original publication. Similar to the data generated with genome skimming techniques based on shallow-depth shotgun genomes, various genomic and transcriptomic resources can be screened for useful molecular phylogenetic markers traditionally characterised with Sanger sequencing. Here, we provide an example of a strategy using reduced-representation genomic as well as transcriptomic data to obtain broad insights into the molecular diversity of the cestode Proteocephalus longicollis, a common parasite of salmonids distributed throughout the Holarctic region. We extract popular mitochondrial and nuclear ribosomal markers from various genomic resources for hundreds of parasite specimens from multiple European whitefish populations and compare those with Proteocephalus representatives from other species of salmonids and various geographical regions. In contrast with the previous morphology-based assessments, molecular phylogeny reveals a high degree of genetic divergence between Proteocephalus isolates from different salmonids, contrastingly low genetic differentiation within the parasite's populations hosted by the European whitefish (Coregonus lavaretus species complex), and a sister species relationship of Proteocephalus from European whitefish and Proteocephalus percae, a parasite of European perch (Perca fluviatilis). Proteocephalus spp. from North American lake whitefish, brown trout and Arctic charr each formed clearly distinct lineages. These results advance our understanding of the interrelationships of the Proteocephalus-aggregate, a well-recognized clade of Holarctic freshwater fish proteocephalids, and support resurrection of some of the nominal species of Proteocephalus, including Proteocephalus exiguus La Rue, 1911 from North American coregonids and Proteocephalus fallax La Rue, 1911 from European C. lavaretus, reserving Proteocephalus longicollis (Zeder, 1800) exclusively for parasites of Salmo trutta.
Keywords: Cestoda; Fish Diseases; Ribosomal RNA; Salmonidae; Taxonomy; zvířata; Genomics; Eucestoda; Mitochondrial genes; Proteocephalus; nemoci ryb; genomika; fylogeneze; Phylogeny; Salmonids; Animals